How green plants make and use food - Coronet (Firm). (Chicago, Illinois Coronet MTI Film & Video, 1984)
All living things depend directly or indirectly on green plants for food and oxygen. Photosynthesis is explored, the difference between food and raw materials and between photosynthesis and cellular respiration is shown.
Advisors, Merrill Gassman, John Smith.
Intended audience: Intermediate and junior high grades.
Keywords: Photosynthesis